Evaluation of a commercial loop-mediated isothermal amplification assay, 3MTM Molecular Detection Assay 2 – Campylobacter, for the detection of Campylobacter from poultry matrices. Issue 3 (4th May 2021) - Rajagopal, R.; Barnes, C. A.; David, J. M.; Goseland, J.; Goseland, J.
ABSTRACT: 1. The objective of this study was to evaluate performance of a commercial loop-mediated isothermal amplification (LAMP) method as an alternative method for the detection of Campylobacter spp. in primary production samples, poultry rinses and raw poultry products, as compared to the US Department of Agriculture Food Inspection Service Microbiology Laboratory Guide Book PCR reference method, MLG 41A. 2. The Campylobacter spp. LAMP was used in conjunction with a ready-to-use enrichment broth that does not require microaerophilic incubation. After enrichment, boot swabs from poultry farms, carcase rinses and raw poultry products were tested by the LAMP method and the MLG 41A PCR method. 3. The ready-to-use enrichment broth enabled the growth of Campylobacter spp. within 22 to 28 hours under aerobic incubation conditions. The LAMP method enabled Campylobacter detection in the enriched samples of various poultry matrices and had equivalent sensitivity and specificity to the MLG 41A PCR method. 4. No significant difference (95% confidence interval) was found between the alternative and the MLG 41A PCR method, as determined by probability of detection analysis, except for neutralising buffered peptone water post-chill rinsates. For the post-chill neutralising buffered peptone water rinsates, the LAMP method had significantly higher confirmed portions.